Characterization of electrospun hydroxyapatite and polycaprolactone composite scaffold / Nur Izzati Aminuddin - Nur Izzati , Aminuddin (2012)
The characteristic and hydrolytic degradation of polycaprolactone-hydroxyapatite composite scaffolds prepared by electrospinning method were studied. In vitro degradation was carried out in phosphate buffered saline (PBS) (pH 7.4 ± 0.1) at 37 ± 1oC for 8 weeks. The extent of degradation was measured by physical mass loss, FESEM observations and FTIR. The results show that the scaffolds were made from a combination of fibers with diameter ranging from 0.5 – 2.5 μm. The surface morphology of scaffolds after 8 weeks of degradation in PBS showed no change (when compared to the ones before the degradation) and this phenomenon was observed in all scaffold compositions. The effect of degradation was also observed by measuring the percentage of mass loss. Almost all the scaffolds showed no mass loss due to water uptake by HA particles (proven from FTIR analyses). Porosity analysis difference with the ones before the degradation. Overall, it can be concluded that PCL/HA composite scaffolds still using ImageJ (NIH, USA) showed that the percentage of porosity of the scaffold is between 27.5%-35.5%. Young’s modulus and ultimate tensile stress (UTS) of the scaffolds showed inconsistent results as the percentage of HA increase. FTIR spectra after degradation showed no retain a relatively stable architecture after 8 weeks of degradation in PBS.